A formação cultural e os temas transversais: um estudo de caso a partir da teoria crítica da sociedade. - Silva, Osvaldo Rocha da (Universidade Federal de São Carlos, 2004)
The National Curricular Parameters were set to guide the education policies of States and Municipal districts and to subsidize the elaboration of the pedagogic proposals of the schools. Aiming that educational institutions form their students for the exercise of the citizenship, the parameters suggest the introduction of work within the social scope so that, when they are approached, they can develop in the students both learning and reflection. Treatment of social subjects would start by their inclusion and complexity of work under transverse themes. This orientation, adopted in the fundamental and medium levels, both in public and private sector schools, is incorporated to the pedagogic proposals of the institutions and starts to address the teachers practice, so that they convert efforts to guarantee the formation for the exercise of citizenship. It was intended in this work to research if in the fundamental teaching of first cycle of a private institution the transverse themes reached the objective of propitiating better cultural formation to the student. In that perspective it was investigated, through a case study developed close to a private school in Piracicaba-SP, how the transverse themes were approached and how much they had contributed for the improvement of students formation. Data analyzed starting from the reflections of Theodor W. Adorno about semi-formation, cultural industry and education, revealed that in the guidelines that oriented the work with the transverse themes, obstacles for the effectiveness of an education aimed at guaranteeing to the individuals, conditions for the development of the critical thought were found. Therefore, besides the efforts of teachers of the researched school in developing pedagogic practice countersigned in the tranverse themes to contribute for the formative process of their students, such efforts resulted exactly the contrary: they corroborated the semi-formation process. This work is intended to contribute to the educators reflection that, pursuing such training, will enable them to form their students, becoming spread vehicles exactly of what they should oppose: an impoverished formation.
Keywords: Escolas particulares; Ensino fundamental; Temas transversais; Teoria crítica; CIENCIAS HUMANAS::EDUCACAO